A biomechanics analysis of the judo osoto-gari technique: comparison of black belt and white belt judokas - Liu, L.; Deguchi, T.; Shiokawa, M.; Ishii, T.; Oda, Y.; Shinya, M. (Sports Biomechanics, 2024)
The purpose of this study was to determine biomechanical factors for the effective execution of the osoto-gari technique by comparing differences between black belt and white belt judokas. Twenty-two male judokas (12 black belts; 10 white belts) performed osoto-gari, and the motion data were recorded using a Mac3D motion analysis system (250 Hz). The peak angular momentums of the trunk and leg of the uke were larger in the black belts than in the white belts, suggesting that the black belts rotated the ukes body more effectively than the white belts. During the swing phase, the peak angular velocities of the arms and trunk twist in the black belts were larger compared to the white belts. During the throwing phase, the black belts had substantially greater peak angular velocities of the arms, upper torso, and trunk twist. Additionally, the timing of the peak value of the upper torso and trunk twist of the black belts was closer to sweeping leg contact than that of the white belts. The results can provide coaches with suggestions for improving training protocol design when teaching osoto-gari and for helping novices more efficiently master the technique.